Design of Quick Query System in Gear Detection Parameter based on Delphi - Zhong Qi; Han Lixi; LI Junwen; Zhong Peipei (Jixie chuandong)
Gears are important parts in mechanical transmission and are widely used.When the gear design is completed，the gear detection parameters need to be determined according to accuracy grade and usage requirements.In general，the look-up table method is used，but according to the latest standards，some parameters need to be calculated.So，it can be seen that the query and calculation of gear parameters are very cumbersome，which brings inconvenience to the design work.Using the Delphi platform to develop a system for quickly querying different types of gear detection parameters，the system provides parameter query for two major types of gears，including cylindrical gears and bevel gears.Through inputting the basic design parameters，the parameters can be automatically and quickly completed.The result can be displayed in the system interface or formed in Excel file to designers.It can greatly improve the accuracy and design efficiency of the gear detection parameter query.Through many engineering design practices，the system is reliable and efficient，and is of great significance to the system design of other related complex computational problems in mechanical design and manufacturing.